Talqiyyan Fikriyyan: An Implementation of Rational Methods in Building Students' Critical Thinking - Sri Mellia Marinda; Muhamad Adhi Maretnas Harapan; Rahmat Kurnia; Muhamad Hanif Abdurrohman (KEDJATI Foundation, 2025)
Critical thinking is a requirement in modern life, especially in the Islamic environment. Islam has ordered humans to think critically to reach the truth. Besides, studies on critical thinking are still being developed in various aspects. In its implementation, mastering critical thinking may face many challenges. This study aims to analyze the problems in building critical thinking and obtain the proper method to teach this skill to students. The data is collected through a literature review related to the study topic. From the review, this study highlights how rational methods can be used fundamentally for all thinking activities, and this method is acquired through the Talqiyyan Fikriyyan concept. In addition, the concept of critical thinking in Islam is a command from Allah Ta’ala (the most glorified, the highest). Also, implementing rational methods in learning builds students’ critical thinking skills. Thus, this study suggests that the Talqiyyan Fikriyyan method can be essential for all subjects in increasing students’ critical thinking skills.